Design and fabrication of integrated soft sensor for soft gripper using multi-material 3D printing - Li, Xin (Nanyang Technological University, 2023)
In the field of soft robotics, integration of sensors into soft, flexible grippers poses significant challenges due to their high-dimensionality and the complexities in developing soft sensors. Selecting suitable sensor types and their placements, while maintaining the dynamics of the soft system, is a critical hurdle.